"Low-Fat" Pseudoangiomatous Spindle Cell Lipoma: A Rare Variant With Loss of 13q14 Region. (December 2015) - Forcucci, Jessica A.; Sugianto, Jessica Z.; Wolff, Daynna J.; Maize, John C.; Ralston, Jonathan S.
Abstract : Abstract: Spindle cell and pleomorphic lipoma constitute a spectrum of lipomatous lesions with characteristic clinical, morphologic, immunohistochemical, and molecular features. Multiple variants have been previously described including vascular, fibrous, plexiform, and those with significantly less fat termed "low-fat" and "fat-free" by Folpe. Cytogenetically, spindle cell lipomas frequently display monoallelic loss of 13q14 region, an abnormality also found in cellular angiofibroma and mammary-type myofibroblastoma. Pseudoangiomatous spindle cell lipoma, originally described by Fletcher et al in 1994, is a rare variant within the spindle cell/pleomorphic lipoma spectrum, with less than 20 published cases. It consists of an admixture of spindle cells, "ropey" collagen, variable amounts of mature fat, and irregular, branching slit-like vascular spaces. The authors present a case of a 1-cm subcutaneous lesion excised from the neck of a 70-year-old man with classic histologic and immunohistochemical features of "low-fat" pseudoangiomatous spindle cell lipoma. Fluorescence in situ hybridization demonstrated a loss of 13q14 region, a characteristic presumed cytogenetic finding of spindle cell lipoma, which has been previously unconfirmed in this variant.